The acquisition of partitive clitics in Romance five-year-olds - Gavarró Algueró, Anna; Guasti, Maria Teresa; Tuller, Laurice; Prévost, Philippe; Belletti, Adriana; Cilibrasi, Luca; Delage, Hélène; Vernice, Mirta (IBERIA: An International Journal of Theoretical Linguistics, 2012)
In this paper we look at a previously unexplored empirical domain: the acquisition of partitive clitics in Catalan, French and Italian. The course of acquisition of third person object clitics is well known and clitic omission is limited to a first stage in the languages in which it is found, so that at age five children do not omit clitics any more, unless they suffer from Specific Language Impairment. Partitive clitics share many properties with third person object clitics and here we develop two experiments, an elicitation and a repetition experiment, of partitive clitics in transitive sentences, and report results for 60 children. Of the two experiments, repetition shows to be the more reliable method, while elicitation gives rise to more pragmatically adequate answers which nevertheless do not present a clitic. The results from both experiments show that partitive clitic omission is not found for any of the languages tested at age five, just like third person object clitics.